Analysis of Visitors’ Perceptions on Circulation Comfort and Accessibility at Masjid Raya Baiturrahman Banda Aceh - Putra, Safriza; Safwan, Safwan; Nursaniah, Cut (Elkawnie, 2025)
Abstract: Studies on spatial comfort and circulation effectiveness in mosque complexes, particularly those integrating universal design principles and national accessibility standards, remain limited in Indonesia. This study aims to assess visitors’ perceptions of spatial comfort and circulation effectiveness in the Baiturrahman Grand Mosque, Banda Aceh, in relation to Permen PUPR No.14/Prt/M/2017. A qualitative descriptive approach was applied, combining field observations, semi-structured interviews with 40 visitors, and spatial layout analysis. Findings reveal that 74% of visitors considered the overall circulation effective, while 26% perceived it as less comfortable or uncomfortable. Key shortcomings include narrow ramps in less strategic locations, escalators that are frequently non-operational, long walking distances to the women’s ablution area, the absence of guiding blocks for visually impaired users, and slippery marble floors during rain. Practical recommendations include widening and relocating ramps, ensuring escalator functionality, installing guiding blocks, applying anti-slip coatings, reducing travel distances for vulnerable groups, and improving signage with larger fonts, higher contrast, and the addition of the Acehnese language. These findings offer empirically grounded recommendations to enhance inclusivity and accessibility in large-scale religious complexes, serving as a reference for architects, facility managers, and policymakers. Abstrak: Kajian mengenai kenyamanan spasial dan efektivitas sirkulasi pada kompleks masjid, khususnya yang mengintegrasikan prinsip desain universal dan standar aksesibilitas nasional, masih terbatas di Indonesia. Penelitian ini bertujuan untuk menilai persepsi pengunjung terhadap kenyamanan spasial dan efektivitas sirkulasi di Masjid Raya Baiturrahman, Banda Aceh, dalam kaitannya dengan Permen PUPR No.14/Prt/M/2017. Pendekatan deskriptif kualitatif digunakan dengan mengombinasikan observasi lapangan, wawancara semi-terstruktur terhadap 40 pengunjung, dan analisis tata ruang masjid. Hasil penelitian menunjukkan bahwa 74% pengunjung menganggap sirkulasi secara keseluruhan efektif, sementara 26% menilai kurang nyaman atau tidak nyaman. Kekurangan utama meliputi ramp yang sempit dan berada di lokasi kurang strategis, eskalator yang sering tidak berfungsi, jarak berjalan yang jauh menuju area wudu perempuan, tidak tersedianya guiding block bagi pengguna tunanetra, serta lantai marmer yang licin saat hujan. Rekomendasi praktis mencakup pelebaran dan relokasi ramp, memastikan eskalator berfungsi, pemasangan guiding block, penerapan lapisan anti-selip, pengurangan jarak tempuh bagi kelompok rentan, serta peningkatan kualitas papan petunjuk dengan huruf lebih besar, kontras lebih tinggi, dan penambahan bahasa Aceh. Hasil penelitian ini menyajikan rekomendasi yang dirumuskan berdasarkan bukti empiris untuk meningkatkan inklusivitas dan aksesibilitas kompleks ibadah berskala besar, serta dapat menjadi acuan bagi arsitek, pengelola fasilitas, dan pembuat kebijakan.